Effect of Light Intensity on Ammonium Removal and Biomass Growth in Different Levels of Aquaculture Effluent Using Duckweed (Lemna perpusilla) - Agus Waluyo; Nirmala, Kukuh; Satya, Awalina; Puji Hastuti, Yuni; Chrismadha, Tjandra; Susanti, Evi; Sumi Lestari, Fajar; Nafisyah, Eva; Sugiarti; Nasrul, Muit (LIMNOTEK Perairan Darat Tropis di Indonesia, 2024)
Cultivating duckweed in aquaculture effluent offers a viable approach to eliminating contaminants. The duckweed biomass obtained can be utilized for the generation of bioenergy. However, elevated levels of ammonium (NH4+) in aquaculture effluent, combined with variations in light intensity, can hinder biomass formation. The precise mechanisms underlying this inhibition remain incompletely elucidated. The study assessed the efficacy of duckweed (Lemna perpusilla) as a treatment agent for wastewater from catfish farms. The objective was to evaluate the growth response of duckweed and its efficacy in reducing ammonium levels. The research demonstrated that daily light intensity fluctuated using shade nets and that the ammonium concentration of aquaculture wastewater varied according to the age of the fish. The shade nets, which blocked 25% of the sunlight and had an average daily light intensity of 3433.34–15199.56 lux, demonstrated a slightly elevated NH4+ removal efficiency and duckweed productivity of 69.34% and 0.050 kg/m²/day, respectively. However, these values were not statistically significant when compared to conditions without shade nets, which had a removal efficiency of 63.97% and duckweed productivity of 0.042kg/m2/day (P<0.05). The implementation of shade structures that effectively decrease solar exposure by 25% shows promise for enhancing duckweed productivity and optimizing nutrient reduction in wastewater from fish cultivation systems. This approach contributes to the promotion of sustainable integrated aquaculture.